Development Of Mining Surrounding Community Through CSR PT NHM As Implementation Of SDG-12 - Ruliyanto Syahrain; Faradisa Bachmid; Faradila Katimen; Firawati Y.Tjan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Negative impacts on the environment arise when human consumption and production increase. Efforts to achieve sustainable consumption and production patterns must align with the objectives of the Sustainability Development Goals (SDGs), especially point 12 of the 17 SDGs, namely Responsible Consumption and Production. Ensuring sustainable consumption and production patterns. CSR programs can be a source and potential to support achieving these goals. This study will explore, dissect, and provide offers on PT Nusa Halmahera Mineral's CSR program, which is seen from the side of its program, which is already in line with supporting the implementation of the 12th Sustainable Development Goal (SDGs-12). One of the CSR programs that can adopt a community development approach in realizing SDGs-12 is the organic and non-organic waste management program. Effective and efficient waste processing can reduce the amount of waste produced and the negative impact of waste on the environment and human health. This type of research is qualitative research using primary and secondary data. The analysis was conducted by reviewing and comparing previous studies on the relationship between SDGs and community development in CSR, as well as the approaches and methods that corporate CSR can apply for waste management.